“Tienda virtual UTC”. - Herrera Llamba, Favio André (2020)
The COVID 19 epidemic forced the country and world trading system to move to virtual environments and communication processes through the internet. The country's economy operations fell because people cannot make the marketing sale of products and services for the sustenance of households, especially those who work under enterprises and small producers who cannot leave their homes to promote their products themselves. For this reason, this project aimed to develop a trading alternative based on technological environments and internet platforms to contribute to the productive development of Latacunga city and the Cotopaxi province. The Literature review allowed us to identify similar applications; however, the analyzed applications require payment so that entrepreneurs can register their product catalogs. The proposed application seeks to build closer links with our province's neediest sectors and continue trade activities, generating new strategies of assistance and service to the community. This research used the Extreme Programming (XP) methodology under the PHP programming environment and Laravel framework. In contrast, the mobile application design used the Mobile-D method programmatically with Android Studio under the focus of Software Engineering. As a result of the design process, a web application is obtained for product and service registration and for delivery service of readily available sold products and friendly graphical user interface that allows effective communication between user and application. Sum up that the proposed technological application aims to continue this social project to strengthen our city and province's productive and commercial support links.